Hollow City - Riggs, Ransom (Philadelphia : Quirk Books, 2014)
Having escaped Miss Peregrine's island by the skin of their teeth, Jacob and his new friends must journey to London (circa 1940), the "peculiar" capital of the world.
Keywords: Orphanages -- Fiction; Escapes -- Fiction; Orphanages -- Fiction; Escapes -- Fiction; Supernatural -- Fiction; London (England) -- Fiction; London (England) -- Fiction